PENGARUH PEMAHAMAN BUKU FIQIH MUYASSAR TERHADAP HASIL BELAJAR FIQIH DI MADRASAH ALIYAH AL IRSYAD PUTRI TENGARAN KAB SEMARANG TAHUN AJARAN 2024/2025 - Yanuar, Aisyah; Rochmawan, Alfian Eko; Syamsuddin, S (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to determine the influence of students understanding of the Fiqih Muyassar book on their learning outcomes in Fiqih. This research uses a quantitative approach. The subjects of this study were 10th grade female students of Madrasah Aliyah Al Irsyad Tengaran. Data collection techniques used in this study were questionnaires and documentation. The data were analyzed using Pearson Product Moment correlation analysis. The prerequisite tests included a normality test and a linearity test. Hypothesis testing was conducted using the Pearson Product Moment correlation and followed by the analysis of the coefficient of determination. The results of this study show that students understanding of the Fiqih Muyassar book does not have a significant influence on their learning outcomes in Fiqih.